Variation in the TNF-alpha promoter region associated with susceptibility to cerebral malaria. - McGuire, W; Hill, A; Allsopp, C; Greenwood, B; Kwiatkowski, D (1994)
Tumour-necrosis factor-alpha (TNF-alpha) is believed to have an important role in the pathogenesis of severe infectious disease and fatal cerebral malaria is associated with high circulating levels of this cytokine. In a large case-control study in Gambian children we find that homozygotes for the TNF2 allele, a variant of the TNF-alpha gene promoter region, have a relative risk of 7 for death or severe neurological sequelae due to cerebral malaria. Although the TNF2 allele is in linkage disequilibrium with several neighbouring HLA alleles, we show that this disease association is independent of HLA class I and class II variation. These data suggest that regulatory polymorphisms of cytokine genes can affect the outcome of severe infection. The maintenance of the TNF2 allele at a gene frequency of 0.16 in The Gambia implies that the increased risk of cerebral malaria in homozygotes is counterbalanced by some biological advantage.